A comparison of two short-course primaquine regimens for the treatment and radical cure of Plasmodium vivax malaria in Thailand. - Pukrittayakamee, S; Imwong, M; Chotivanich, K; Singhasivanon, P; Day, N; White, N (2010)
Thai adult males (N = 85) with acute Plasmodium vivax malaria and normal glucose-6-phosphate dehydrogenase screening were randomized to receive 30 mg or 60 mg primaquine daily for 7 days (N = 43 and 42, respectively). The regimens were well tolerated and all patients recovered fully. Median fever clearance (47 hours; range 4 to 130 hours), mean + or - SD parasite clearance times (87.7 + or - 25.3 hours), gametocyte clearance, and adverse effects were similar in the 2 groups. Two patients, 1 from each group, had a 30% reduction in hematocrit. The cumulative 28 day relapse rate (95% confidence interval) by Kaplan Meier survival analysis was 29% (16-49%) in the 30 mg group compared with 7% (2-24%) in the 60 mg group; P = 0.027. Comparison with previous data obtained at this same site suggests that the recurrences comprised approximately 17% recrudescences and 12% relapses in the 30 mg/day group compared with 3% recrudescences and 4% relapses in the 60 mg/day group. These data suggest that the dose-response relationships for primaquine's asexual stage and hypnozoitocidal activities in-vivo are different. A 1 week course of primaquine 60 mg daily is an effective treatment of vivax malaria in this region.